1990
DOI: 10.1055/s-2007-1006811
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of the Venous Flap: Investigation of the Recipient Vein

Abstract: In previous studies using rabbit ears, total venous perfusion flaps (TVPF) were used that did not contain in the experimental model any chosen arteries truly representative of clinical venous flaps. We discovered that the TVPF could survive even under conditions of poor blood circulation. In the present study, conditions of the recipient veins were investigated using flow-through veins in TVPFs of rabbit ears and human dorsal digital veins. The research suggested that conditions for TVPF survival are a high de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Although our experimental models were different from Baek's, we reported that the veins of flow-through venous flaps in the rabbit ear had 2.2 ± 0.42 mmHg venous pressure and clinically, veins from the dorsum of the finger to the dorsum of the hand, (which was selected as the recipient site) had venous pressures two to three times higher than rabbit-ear veins (venous pressure of the dorsum of the finger-, afferent venous pressure 5.9 ± 2.4 mmHg; efferent venous pressure 2.9 ± 1.0 mmHg). 3 From this, we deduce that a dense venous network alone will allow a flow-through venous flap, more than 1.10 ± 0.48 cm in width (the value validated experimentally) to survive in clinical cases. In any case, it is significant that the survival width and area of the flowthrough venous flap has been measured quantitatively.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Although our experimental models were different from Baek's, we reported that the veins of flow-through venous flaps in the rabbit ear had 2.2 ± 0.42 mmHg venous pressure and clinically, veins from the dorsum of the finger to the dorsum of the hand, (which was selected as the recipient site) had venous pressures two to three times higher than rabbit-ear veins (venous pressure of the dorsum of the finger-, afferent venous pressure 5.9 ± 2.4 mmHg; efferent venous pressure 2.9 ± 1.0 mmHg). 3 From this, we deduce that a dense venous network alone will allow a flow-through venous flap, more than 1.10 ± 0.48 cm in width (the value validated experimentally) to survive in clinical cases. In any case, it is significant that the survival width and area of the flowthrough venous flap has been measured quantitatively.…”
Section: Discussionmentioning
confidence: 61%
“…It is also necessary that the ear vein, when acting as a pedicle, should have arterial rather than venous characteristics, i.e., good venous pressure and high venous oxygen tension. 3 However, it has also been reported that the measurement of blood flow in the flowthrough venous flap is not possible just after surgery, 4 and no studies have been done on what size flap can survive with only one flow-through vein. Spindly and thin flaps have been raised on a single venous pedicle in many clinical cases, while different survival rates have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…the most common complication and a leading cause of venous flap failures. [12][13][14][15][16][17] Four types of venous flaps have been described, based on whether the inflow and outflow vessels are arterial or venous: veno-venous (v-v); arterio-venous (a-v), pedicle venous, and arterio-arterial (a-a). Many of the clinical experiences that have been reported have been with the veno-venous flaps (v-v) or the arteriovenous (a-v) venous flaps in soft-tissue reconstruction of the fingers, hands, extremities, and head and neck.…”
Section: Discussionmentioning
confidence: 99%
“…Arterialized venous flaps are thought to do better because of the higher level of oxygenation. 13,15,17 However, if known artery-based flaps are either not available or not suitable, venous flaps can be excellent options.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the success of the pure venous flap, 3 " 16 ' 20 " 25 the mechanisms of its blood circulation has not been well understood. For example, it is not clear whether there is capillary perfusion immediately following transfer.…”
mentioning
confidence: 99%